2014
DOI: 10.1186/1470-7330-14-24
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation into the clinical impact of 4D-PET/CT in the characterisation of solitary pulmonary nodules

Abstract: Background While the effects of respiratory motion on measuring metabolic signal in PET/CT scanning are well known, it is still standard practice in most centres to scan patients while breathing freely with no correction for the effects of respiratory motion. The aim of this study was to investigate the impact of 4D-PET/CT in classifying lesions in patients with a radiologically-indeterminate solitary pulmonary nodule. Methods Twenty consecutive patients with a solitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Such artifacts impede the provision of appropriate patient care. For example, use of fluorine 18 FDG PET/ CT for oncologic imaging is subject to the limitations and artifacts imposed by respiratory motion; subsequent corrections could affect initial staging and subsequent treatment response monitoring, thus altering patient management, as previously shown (33,34). The objective improvements we saw in image resolution (decreased lesion FWHM) and quantification of radiotracer uptake (increased FDG SUV max ) Note.-ND = lesion not definable with a FWHM measurement (eg, lesion-to-background ratio was too low), SD = standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Such artifacts impede the provision of appropriate patient care. For example, use of fluorine 18 FDG PET/ CT for oncologic imaging is subject to the limitations and artifacts imposed by respiratory motion; subsequent corrections could affect initial staging and subsequent treatment response monitoring, thus altering patient management, as previously shown (33,34). The objective improvements we saw in image resolution (decreased lesion FWHM) and quantification of radiotracer uptake (increased FDG SUV max ) Note.-ND = lesion not definable with a FWHM measurement (eg, lesion-to-background ratio was too low), SD = standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…179,180 Furthermore, 4D PET imaging with fluorodeoxyglucose (FDG) tracers is just as limited as 3D PET imaging, in terms of not having the ability to differentiate malignancies from inflammatory processes, correct for partial volume effects or correct for lesions that are inherently less FDG-avid. 181 Kruis et al 182 also demonstrated the importance of using a 4D-CT (vs a 3D CT) for the attenuation correction of the 4D PET because of the uncertainties that may be introduced into the SUV values due to respiratory-induced CT changes.…”
Section: C1 Techniques and Existing Uncertaintiesmentioning
confidence: 99%
“…For the first method, to maintain image quality, respiratory gating requires a longer scan time and/or a higher injected activity. Therefore, respiratory gating is nowadays not routinely used for diagnostic imaging [ 49 , 50 ]. However, it is more commonly applied for radiotherapy planning, where an accurate delineation and quantification is even more important [ 51 – 53 ].…”
Section: Introductionmentioning
confidence: 99%